UPAYA PERAWATAN PERALATAN KESEHATAN DALAM RANGKA MENJAGA DAN MENINGKATKAN MUTU PELAYANAN KESEHATAN DI PUSKESMAS TAMPAKSIRING II - I Made Agus Mahardiananta; Suhartono Suhartono; Cokorda Istri Dharmayanti (Universitas Mataram, 2022)
The quality of health services must always be improved for the realization of a good public health degree. One of the things that can be done is to maintain the quality of the available health facilities and equipment. Indicators of quality medical devices include guaranteed accuracy, accuracy and safety in their use. There are several medical devices that are often used, such as ECG, flumeter regulator, digital sphygmomanometer, dry sterilizer, examination lamp and UV lamp, which are important elements that maintain the continuity of public health services. This community service activity aims to maintain and repair medical devices and is a training for technicians and medical personnel. It will also improve skills in managing medical equipment. The method used is observation, lectures on calibration material, inventory and direct practice of repairing medical devices. This activity can be followed by all health workers at the puskesmas with the hope that the responsibility for medical equipment is not only owned by technicians, but becomes the responsibility of other health workers as well. The activity that has been carried out in this service is an inventory of tools to make it easier to check and repair medical devices. The tools that have problems are experimentation lamps and UV lamps. On the examination lamp, the lamp was damaged and it can be reused by replacing the lamp. Meanwhile, the UV lamp damaged the transformer and fittings, after replacing these components the UV lamp can be used again. This activity indirectly provides knowledge and lessons in the form of experience. As well as adding insight into the operation of medical devices at the Tampaksiring II Health Center. Increased knowledge of service participants can be seen from their ability to directly participate in repairing medical devices.